Distinct evolutionary strategies in the GGPPS family from plants - Coman, Diana; Altenhoff, Adrian; Zoller, Stefan; Gruissem, Wilhelm; Vranová, Eva (Frontiers in Plant Science, 2014)
Multiple geranylgeranyl diphosphate synthases (GGPPS) for biosynthesis of geranylgeranyl diphosphate (GGPP) exist in plants. GGPP is produced in the isoprenoid pathway and is a central precursor for various primary and specialized plant metabolites. Therefore, its biosynthesis is an essential regulatory point in the isoprenoid pathway. We selected 119 GGPPSs from 48 species representing all major plant lineages, based on stringent homology criteria. After the diversification of land plants, the number of GGPPS paralogs per species increases. Already in the moss Physcomitrella patens, GGPPS appears to be encoded by multiple paralogous genes. In gymnosperms, neofunctionalization of GGPPS may have enabled optimized biosynthesis of primary and specialized metabolites. Notably, lineage-specific expansion of GGPPS occurred in land plants. As a representative species we focused here on Arabidopsis thaliana, which retained the highest number of GGPPS paralogs (twelve) among the 48 species we considered in this study. Our results show that the A. thaliana GGPPS gene family is an example of evolution involving neo- and subfunctionalization as well as pseudogenization. We propose subfunctionalization as one of the main mechanisms allowing the maintenance of multiple GGPPS paralogs in A. thaliana genome. Accordingly, the changes in the expression patterns of the GGPPS paralogs occurring after gene duplication led to developmental and/or condition specific functional evolution.